Handbook of toxicology - Derelanko, Michael J.; Auletta, Carol (CRC Press, Taylor and Francis, 2014)
"This third edition of a classic volume contains contributions from experts who provide both fundamental and applied information. Providing a fresh perspective on several topics, this edition contains completely rewritten chapters on immunotoxicology and endocrine, reproductive, and developmental toxicology. Chapters on neurotoxicology, and inhalation and regulatory toxicology have been updated and consolidated. The format of the book is designed to allow working toxicologists to locate basic information quickly. A separate glossary is included with terms presented both alphabetically and by toxicological subspecialty"--Provided by publisher.